2006
DOI: 10.1111/j.1742-4658.2005.05080.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene duplication and separation of functions in αB‐crystallin from zebrafish (Danio rerio)

Abstract: The a-crystallins are evolutionarily related members of the small heat shock protein (sHSP) superfamily which are taxonomically ubiquitous components of the vertebrate eye lens [1]. The aA-crystallin and aB-crystallin genes arose through a gene duplication event that occurred early in vertebrate history and are most closely related to sHsp20 [2]. Mammalian aA-crystallin is primarily lens specific and has lost the stress induction response that characterizes most sHsps, although some metals induce its expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 41 publications
1
42
1
Order By: Relevance
“…We also isolated a second ␣B-crystallin gene, which we called ␣Bb-crystallin (cryabb; GenBank Accession Number, AY939876). This gene is identical to ␣B2-cystallin (GenBank Accession Number; DQ113417) (Smith et al, 2006) and similar to a previously reported ␣B1-crystallin (GenBank Accession Number, NM 131157) (Posner et al, 1999).…”
Section: Two-dimensional Gel Electrophoresis Reveals Diminished Crystmentioning
confidence: 55%
See 2 more Smart Citations
“…We also isolated a second ␣B-crystallin gene, which we called ␣Bb-crystallin (cryabb; GenBank Accession Number, AY939876). This gene is identical to ␣B2-cystallin (GenBank Accession Number; DQ113417) (Smith et al, 2006) and similar to a previously reported ␣B1-crystallin (GenBank Accession Number, NM 131157) (Posner et al, 1999).…”
Section: Two-dimensional Gel Electrophoresis Reveals Diminished Crystmentioning
confidence: 55%
“…The membranes were incubated with antimouse ␣A-crystallin antisera (1/2000 dilution) or anti-newt ␥-crystallin antisera (1:2000 dilution) followed by HRP-conjugated anti-guinea pig IgG (Jackson ImmunoResearch Laboratories, 1:5000) or anti-rabbit IgG (Amersham Pharmacia Biotech; 1: 10,000), and visualization with enhanced chemiluminescence (Perkin Elmer Life Science). The specificity of each antibody was confirmed by western blotting of lysates prepared by transiently transfecting Chinese Hamster Ovarian cells (American Type Culture Collection) with expression constructs of zebrafish ␣A- (Runkle et al, 2002) (GenBank Accession Number, NM 152950), ␣B1- (Posner et al, 1999;Smith et al, 2006) (GenBank Accession Number, NM 131157), ␤B1- (Chen et al, 2001) (GenBank Accession Number, NM 173231) and ␥-crystallin genes. Cell maintenance and gene transfection procedures were as described previously (Goishi et al, 2003).…”
Section: Western Blotsmentioning
confidence: 99%
See 1 more Smart Citation
“…In adults, αB1-crystallin transcripts were largely restricted to the lens tissue, while αB2-crystallin transcription was identified in brain, heart, liver and skeletal muscle, in addition to the lens (Posner et al, 1999;Smith et al, 2006). This suggests the expression patterns of the zebrafish αB-crystallins may change between development and the adult, although more detailed analysis of the gene and protein expression patterns will be necessary to fully examine this possibility.…”
Section: Lengsin Expression Patterns During Zebrafish Lens Formation mentioning
confidence: 95%
“…sHsps have been identified in the zebrafish, ten of which are likely orthologs of human sHsps, and each of which corresponds to one of the thirteen teleost sHSPs (Franck et al, 2004). Through searching all available expressed gene and genomic sequence databases, seven additional zebrafish sHsps exist (Hspb1, Hspb2, Hspb3, Hspb4, Hspb5a, Hspb5b, and Hspb12) (Posner et al, 1999;Franck et al, 2004;Mao et al, 2005;Smith et al, 2006). The zebrafish protein is 57% similar to human Hsp27, 56% similar to mouse Hsp25 and 64% similar to an Hsp27 protein cloned from the desert topminnow, Poeciliopsis lucida (Norris et al, 1997).…”
Section: Genomic Structurementioning
confidence: 99%